1982
DOI: 10.1007/bf00252849
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the outcome of an educational programme of diabetes self-care

Abstract: The efficacy of our current educational programme for diabetic patients was assessed. Cognitive and behavioural tests were administered to 75 Type 1 (insulin-dependent) diabetic patients, aged less than or equal to 30 years attending the Diabetic Clinic of the Mater Misericordiae Hospital, Dublin, Ireland. An overall deficiency in knowledge was evident. Fifty-one patients responded incorrectly to greater than 20% of the items tested. Twenty-nine patients lacked the ability to communicate a simple understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 16 publications
0
10
1
1
Order By: Relevance
“…10 However, in our evaluation, knowledge increment from phase A to phase B did not correlate with final level of glycemic control, although significantly only in NIDDM patients. Nevertheless, the low order of this correlation suggests that only part of the benefit of computer-based learning is likely to be mediated by knowledge increment.…”
Section: Resultsmentioning
confidence: 85%
“…10 However, in our evaluation, knowledge increment from phase A to phase B did not correlate with final level of glycemic control, although significantly only in NIDDM patients. Nevertheless, the low order of this correlation suggests that only part of the benefit of computer-based learning is likely to be mediated by knowledge increment.…”
Section: Resultsmentioning
confidence: 85%
“…Although knowledge alone does not guarantee requisite behavior modifications or effective self-management (10,11), the assessment of diabetes-related knowledge is an important first step from which to individualize diabetes education programs and make evaluations of their effectiveness (12). However, there are few reliable and valid instruments with which to measure outcomes, particularly for individuals who speak a language other than English.…”
mentioning
confidence: 99%
“…Studies have demonstrated that knowledge about medications, diet, exercise, home glucose monitoring, foot care, and treatment modifications is necessary to effectively selfmanage diabetes [12,13]. Although knowledge alone does not guarantee requisite behaviour modifications or effective self-management [14], the assessment of diabetes self-care related knowledge is an important first step from which to individualize diabetes education programs and make evaluations of their effectiveness [15].…”
Section: Introductionmentioning
confidence: 99%